ANALISIS HUBUNGAN PENGHINDARAN PAJAK DAN BIAYA HUTANG SERTA KEPEMILIKAN INSTITUSI SEBAGAI VARIABEL MODERASI - Heryawati, Elma; Indriani, Rini; Midiastuty, Pratana Puspa (UNIB Press, 2018)
This thesis examines the Relation Analysis of tax avoidance and cost of debt on manufacturing company in Indonesia in 2008-2010, and also analysis influence of institutional ownership on the relationship tax avoidance and cost of debt. The result are there is a substitution relationship between tax avoidance and cost of debt on real estate company in Indonesia in 2013-2016. And institusional ownership is not strengthening the relationship between tax avoidance and cost of debt.